Association between anxiety and aggression in adolescents: a cross-sectional study - Jee Eun Chung (BMC Pediatrics, 2019)
Abstract Background The purpose of this study was to investigate the relationship between anxiety proneness and aggressive behavior in adolescents. Methods A quantitative, large scale cross-sectional study was conducted in Korea. The survey questionnaire included general health behavior and scales for assessing anxiety (Revised Children’s Manifest Anxiety Scale; RCMAS) and aggressive behavior (The Aggression Questionnaire; AQ) in adolescents. Results A total of 2432 students participated in the survey, and 1933 individuals completed the questionnaire, indicating a response rate of 79.5%. Based on RCMAS, 163 (8.4%) subjects were classified as the anxiety group. Aggressive behavior was significantly associated with higher anxiety scores. In particular, among four subdomains of aggression, anger and hostility had a stronger relationship with anxiety than did physical and verbal aggression. Multivariate analysis demonstrated that anxiety was independently associated with gender, age, headache, constipation, asthma, and aggression score. Adolescents with total aggression scores of 69 or higher showed a 9-fold (AOR = 9.00, CI = 6.33–13.51) higher risk of anxiety compared to those with under 69. Conclusion Aggression and anxiety are important aspects of mental health in adolescents. Our results demonstrated that higher risk of anxiety was associated with total aggression scores. In particular, indirect aggression (i.e. anger and hostility) was more closely associated with anxiety than direct aggression.